2007
DOI: 10.1111/j.1525-1438.2007.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in Thai women with early-stage cervical cancer after radical hysterectomy

Abstract: We determined the prevalence of sexual dysfunction in women with early-stage cervical cancer who had undergone radical hysterectomy in three institutions of Thailand. An interview was conducted according to the structured questionnaire composing of seven domains of sexual function: frequency, desire, arousal, lubrication, orgasm, satisfaction, and dyspareunia. From 105 women included in the study, mean age was 45.3 +/- 7.8 years. Seventy-five (71.4%) were in premenopausal period. Eight out of 105 women (7.6%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 14 publications
3
48
1
Order By: Relevance
“…The findings on age as an important predictor of unmet needs in this population lend support to other research noting this association (Tangjitgamol et al, 2007;McCallum et al, 2012). Younger participants appear to be experiencing greater difficulty with unmet emotional, sexual, and social needs, suggesting that interventions surrounding themes such as fertility, relationships/intimacy, gender/family roles, and anxiety are needed for this population (see also Zabrack, 2011).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The findings on age as an important predictor of unmet needs in this population lend support to other research noting this association (Tangjitgamol et al, 2007;McCallum et al, 2012). Younger participants appear to be experiencing greater difficulty with unmet emotional, sexual, and social needs, suggesting that interventions surrounding themes such as fertility, relationships/intimacy, gender/family roles, and anxiety are needed for this population (see also Zabrack, 2011).…”
Section: Discussionsupporting
confidence: 57%
“…The finding that radiation therapy did not predict higher needs was surprising, given the well-documented literature on physical post-radiation vaginal changes (Jensen et al, 2004a;Tangjitgamol et al, 2007). This result may be explained by an over-representation of ovarian cancer patients who likely received chemotherapy and an underrepresentation of groups of patients receiving radiation therapy as a primary treatment in the present sample.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…This procedure includes removal of the uterus, upper vagina, and uterosacral ligaments with ligation of the uterine artery at its origin and resection of the parametrium, and pelvic lymphadenectomy [2]. Radical hysterectomy is associated with significant postoperative morbidity including blood loss, bladder dysfunction, sexual dysfunction, and bowel dysfunction [3,4,5]. Much of this morbidity is due to the removal of the parametrial tissue, which contains autonomic nerve fibers that play a critical role in bladder, sexual, and bowel function [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A study involving young patients in Thailand revealed only a minimal effect of radical hysterectomy on sexual function; however, only 46 % of these patients also had undergone surgical menopause [ 98 ]. Frumovitz et al, who evaluated 114 women at least 5 years after completion of treatment, reached a similar conclusion.…”
Section: Arguments Against Routine Screening For Sexual Dysfunction Nmentioning
confidence: 92%